Evaluation of the physicochemical characteristics of mango, artificially matured with calcium acetylide - Tuárez-García, Diego; Erazo-Solórzano, Cyntia; Vera-Chang, Jaime; Solórzano-Menéndez, Martín; Vásquez-Cortez, Luis; Alvarado-Vásquez, Kerly (Revista Colombiana de Investigaciones Agroindustriales, 2022)
The use and application of low-cost artificial ripening agents are common among producers and traders because the results obtained are acceptable, however, due to the lack of methodology, they are used in disproportionate doses, without foreseeing the implication that it has on the characteristics of the fruit. The main objective is to evaluate the physical-chemical properties of two varieties of mango (Mangifera indica), Tommy Atkins and Kent, subjected to artificial ripening with a chemical agent (calcium acetylide CaC2). For the experiments, two varieties of mango in a state of uniform physiological maturity were used, relating them to three doses of the ripening agent. For ripening, the fruits were conditioned in wooden boxes where time, temperature, and humidity were monitored. The variables analyzed are Brix, pH, moisture, energy, protein, acidity, texture, and fiber. The results obtained highlight that, regardless of the diversity, both in physical limits and in chemical limits of the fruit, those who were subjected to a dose of 10 g/kg of fruit for a period of 48 hours of exposure in a hermetically sealed environment stood out, controlling that the temperature is between 27.7 °C and relative humidity between 90 %. It is essential to highlight that the maturation time of the frit was accelerated by two days according to the dosage used.